2017
DOI: 10.1016/j.marpolbul.2016.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Blood and feather concentrations of toxic elements in a Baltic and an Arctic seabird population

Abstract: We report blood and feather concentrations of elements in the Baltic Sea and Arctic population of common eiders (Somateria mollissima). The endangered Baltic Sea population of eiders was demonstrably affected by element pollution in the 1990s. While blood concentrations of Hg were higher in Baltic breeding eiders, blood Se, As and Cd concentrations were higher in Arctic eiders. Blood concentrations of Pb, Cr, Zn and Cu did not differ between the two populations. While blood Pb concentrations had declined in Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 66 publications
(87 reference statements)
1
2
0
Order By: Relevance
“…Thus, the results of the present research contradict more conservative values considered safe in bird blood, such as 35 µg/dL (Klein and Galey, 1989) and 30 µg/dL (Pain et al, 1993), while corroborating with the most recent blood lead level value of 20 µg/dL considering a normal threshold value for subclinical signs (Bauck and LaBonde, 1997;Dumonceaux and Harrison, 1994;Fenstad et al, 2017;Franson and Pain, 2011;López-Perea et al, 2019;Monclús et al, 2020). It should be noted that a limitation of the study is the small number of birds included in the samples.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Thus, the results of the present research contradict more conservative values considered safe in bird blood, such as 35 µg/dL (Klein and Galey, 1989) and 30 µg/dL (Pain et al, 1993), while corroborating with the most recent blood lead level value of 20 µg/dL considering a normal threshold value for subclinical signs (Bauck and LaBonde, 1997;Dumonceaux and Harrison, 1994;Fenstad et al, 2017;Franson and Pain, 2011;López-Perea et al, 2019;Monclús et al, 2020). It should be noted that a limitation of the study is the small number of birds included in the samples.…”
Section: Resultssupporting
confidence: 83%
“…On the other hand, a large portion of the most recent studies have indicated that lead concentrations in the blood of birds that do not show subclinical signs should be less than 20 µg/dL (Bauck and LaBonde, 1997;Dumonceaux and Harrison, 1994;Fenstad et al, 2017;Franson and Pain, 2011;López-Perea et al, 2019;Monclús et al, 2020) and as threshold concentrations of clinical poisoning and lethality probability set as 50 µg/dL (Monclús et al, 2020;Temamogullari et al, 2022). Other studies even present more cautious results, highlighting that blood lead level above 10 µg/dL is considered a risk limit for the health of chickens (Yuan and Tang, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the energetic perspective, prey are the primary source of environmental pollutants for white-tailed eagles in the Baltic Sea (HELCOM, 2018). Contaminant composition can vary temporally and spatially but also between species (Airaksinen et al, 2015;Fenstad et al, 2016Fenstad et al, , 2017Hallikainen et al, 2004Hallikainen et al, , 2011HELCOM, 2010). The great variation between pairs in both diet breadth and in what type of prey the diet contains enables us to ask questions both about the importance of variation per se and of specific prey species or groups, and their associated environmental conditions.…”
Section: Introductionmentioning
confidence: 99%